Inferior Turbinate Surgery: Difficulties Between the Decision-Making and the Selection of Proper Technique - Mohamed Bofares Khaled (Journal of Otolaryngology Advances, 2022)
Back ground and Objectives The inferior conchae have important role in the maintenance of nasal airflow via providing the nasal valve mechanism but increase of inferior turbinate bulk may result in significant nasal obstruction. Therefore, this may need further surgical intervention to deal with these bulky conchae but it is very necessary to balance between the mechanical as well as the functional patency of the nose. Thus, through this surgery it become difficult to decide whether the patient is a candidate for surgery and which technique is suitable for that particular patient. Patients and Methods Two- thousands three- hundreds and six patients aged 3-65 years of hypertrophied inferior conchae, had been diagnosed as a cases of mechanical nasal obstruction due to hypertrophied inferior conchae (HIC). The patients operated by two techniques of inferior conchae surgery, which are sub-mucosal diathermy (SMD) and partial inferior turbinectomy (PIT). The outcomes were correlated to different factors to assess as much as possible the clear conclusion for this significant issue in rhinology. Results and Conclusion The proper selection of patient for this pattern of surgery is considered as one of main aspects of this issue and one of significant steps toward the resolving of this dilemma it is very necessary to select the most suitable candidate for this surgery. On the other hand, the type of the technique for this surgery is needed to be selected probably.
Keywords: Inferior concha surgery